Academic self-efficacy, learning styles and motivational factors as correlates of academic achievement of high ability secondary school students in Owerri, Imo State (2022)
The academic achievement of students is an important indicator of the academic success in school. Some high-ability students exhibit a discrepancy between their potential and achievement thereby demonstrating negative abilities and low achievement in their academic pursuit. It has however been noted that some cognitive and psychological factors such as academic self-efficacy, learning styles and motivational factor contribute to superlative performance of high- ability students. This study, therefore, investigated the relationship among academic self-efficacy, learning style, motivational factor and academic achievement of high-ability students in senior secondary schools Owerri, Imo State, Nigeria. This study adopted a descriptive survey research design of correlational type. Multi-stage sampling technique was used to select 240 respondents with high-ability from the sampled schools in Owerri, Imo State. Inferential Statistics of Multiple Regression Analysis (MRA) and Pearson Product Moment Correlation, (PPMC) were used for data analysis. The instruments used in the study are Slosson Intelligence Test (SIT), English Language and Mathematics Achievement Test (ELMA), Student’s Academic Record (STAR), Motivational factor Scale (MAS), Academic Self-efficacy Scale (ASS) and Leaming Style Scale (LSS). The result showed that there is a significant relationship among academic achievement of high-ability students and academic self-efficacy (r=.554, p(.000)<.05), motivational factor (r=.720, p(.000)<05), and learning styles (r=.717, p(.000)<.05) respectively and are related to academic achievement among high-ability students in Owerri: Hence, there is a positive significant relationship between the independent variables and the dependent variable. This implies that academic self-efficacy, motivational factor, and learning styles improve academic achievement. Therefore, it was recommended that teachers of high-ability students should expose their students to the relevance of academic self-efficacy, learning styles and motivational factor to the academic achievement of high-ability students.